Monitoring and Evaluation Practices and Performance of livelihood ventures: Focus; Nairobi youths conservation projects, Kenya - Wanjiru, Nderitu B.; Kyalo, Dorothy Ndunge; Mulwa, Angeline Sabina; Mbugua, John (European Scientific Journal, ESJ, 2020)
In Kenya, youth unemployment rate is on the rise especially for urban youths, despite government’s perennial interventions and funding. This study sought to investigate on monitoring and evaluation practices and performance of livelihood ventures; focusing on youth conservation projects in Nairobi County. The study specifically focused on solid waste collection projects managed by youth groups within Nairobi residential areas; which is among the conservation projects that attract government funding through the Directorate of youth. The study had a target population of 700 youth group members and a Study sample of 248 youths. Key informants from 4 departments of Directorate of Youth affairs were purposely selected. The study adopted descriptive survey and correlational research designs where data was collected using questionnaire and focus group discussion guide. Qualitative data was analyzed and presented in narrative statements while inferential statistics were analyzed using Pearson correlation coefficient and multiple regression analysis to test hypotheses. The research formulated a hypotheses in null state and subsequently, F-Test was used test it portraying; r (247) =.196, R2 0.38, F (5,242) = 9.777 p≤.05, implying that the levels of monitoring and evaluation practices possessed by youths may be a good predictor of performance of youth conservation projects. This inferred to the rejection of the null hypothesis and the conclusion made that H1: There is a significant relationship between monitoring and evaluation practices and performance of youth solid waste management projects in Nairobi County. The study findings provided the evidence that the level of performance increases as monitoring and evaluation practices intensifies. The researcher recommends a Policy action by government to incorporate youths to obtain and nature monitoring and evaluation skills through industrial attachments in National and County entities dealing with conservation projects; to enhance gainful youth conservation projects.